Asset Price Effects of Peer Benchmarking : Evidence from a Natural Experiment - Acharya, Sushant (World Bank, Washington, DC, 2015)
This paper estimates the effects of peer benchmarking by institutional investors on asset prices. To identify trades purely due to peer benchmarking as separate from those based on fundamentals or private information, the paper exploits a natural experiment involving a change in a government imposed underperformance penalty applicable to Colombian pension funds. This change in regulation is orthogonal to stock fundamentals and only affects incentives to track peer portfolios allowing the authors to identify the component of demand due to peer benchmarking. The authors find that peer effects among pension fund managers generate excess in stock return volatility, with stocks exhibiting short-term abnormal returns followed by returns reversal in the subsequent quarter. Additionally, peer benchmarking produces an excess in comovement across stock returns beyond the correlation implied by fundamentals.